Avaliando os efeitos de uma audiência punitiva versus de uma audiência não punitiva sobre a acurácia do relato verbal de crianças - Silva, Joice Cristina Cintra (Universidade Federal de São Carlos, 2023)
The present study evaluated the effects of two different audience functions (punitive and non-punitive), whose discriminative functions were established experimentally, on the accuracy of children's verbal reports. Six typically developing children aged between eight and 10 years participated; however, the data from only three participants, who met the inclusion criteria, were considered for the analysis. "Doing" consisted of shooting at a target in a computerized game and "saying" consisted of reporting their successes and errors by clicking on one of two colored squares displayed on the screen after each trial (green for reporting successes and red for reporting errors). At the end of each session, the participant reported the number of points obtained during the task for the current audience (punitive or non-punitive). The experimental conditions were: 1) Baseline, which assessed the correspondence of the report in the absence of the different audiences and without programmed differential consequences ; 2) Establishment of the punitive and non-punitive discriminative functions of the audiences, which experimentally established the discriminative functions of the audiences (punitive and non-punitive) and 3) Test of the discriminative functions of the audiences, which assessed the correspondence of the report as a function of the different audiences, without programmed consequences. An adapted alternating treatment design was used to compare the effects of the two different audiences and a multiple baseline design across participants to compare the effect of introducing the different audiences in relation to the control condition. The data were analyzed in terms of the percentage of corresponding reports of errors during the computer game and the correspondence of the final report about the total points obtained for the different audiences at the end of each session. The results showed that two of the three participants showed an increase in the levels of correspondence of the reports made during the computerized game when the audiences were introduced. However, the levels of correspondence were not differentially influenced by the different functions of the audiences in the study. Parameters of the procedure for establishing the discriminative functions of the audiences were discussed as a factor to be better investigated in future studies.
Evaluating the effects of a punitive versus a non-punitive audience on children's verbal reports accuracy
Keywords: Audiência; Comportamento verbal; Correspondência fazer-dizer; Relato verbal; Audience; Verbal behavior; Do-say correspondence; Verbal report; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL